Impaired glucose tolerance in first-episode drug-naïve patients with schizophrenia: relationships with clinical phenotypes and cognitive deficits. Issue 15 (8th September 2016) - Chen, D. C.; Du, X. D.; Yin, G. Z.; Yang, K. B.; Nie, Y.; Wang, N.; Li, Y. L.; Xiu, M. H.; He, S. C.; Yang, F. D.; Cho, R. Y.; Kosten, T. R.; et al.
Abstract : Background: Schizophrenia patients have a higher prevalence of type 2 diabetes mellitus with impaired glucose tolerance (IGT) than normals. We examined the relationship between IGT and clinical phenotypes or cognitive deficits in first-episode, drug-naïve (FEDN) Han Chinese patients with schizophrenia. Method: A total of 175 in-patients were compared with 31 healthy controls on anthropometric measures and fasting plasma levels of glucose, insulin and lipids. They were also compared using a 75 g oral glucose tolerance test and the homeostasis model assessment of insulin resistance (HOMA-IR). Neurocognitive functioning was assessed using the MATRICS Consensus Cognitive Battery (MCCB). Patient psychopathology was assessed using the Positive and Negative Syndrome Scale (PANSS). Results: Of the patients, 24.5% had IGT compared with none of the controls, and they also had significantly higher levels of fasting blood glucose and 2-h glucose after an oral glucose load, and were more insulin resistant. Compared with those patients with normal glucose tolerance, the IGT patients were older, had a later age of onset, higher waist or hip circumference and body mass index, higher levels of low-density lipoprotein and triglycerides and higher insulin resistance. Furthermore, IGT patients had higher PANSS total and negative symptom subscale scores, but no greater cognitive impairment except on the emotional intelligence index of the MCCB. Conclusions: IGT occurs with greater frequency in FEDN schizophrenia, and shows association with demographic and anthropometric parameters, as well as with clinical symptoms but minimally with cognitive impairment during the early course of the disorder.